Estudo térmico e de materiais na construção de casas populares com blocos confeccionados a partir de um composto a base de cimento, gesso, eps e raspa de pneu - Silva, André da Rocha (2010)
We built an experimental house on an UFRN´s land using blocks made by a composite consisting of cement, plaster, EPS, crushed rubber and sand. Several blocks were made from various compositions and we made preliminary tests of mechanical and thermal resistance, choosing the most appropriate proportion. PET bottles were used inside the block to provide thermal resistance. In this work, a second function was given to the bottles: to serve as a docking between the blocks, because the ends of the cylinders came out of each block on top as well as at the bottom, with the bottom cut, allowing to fit of the extremities of the upper cylinder of a block in the lower holes of the other one, which were formed by the cutting already mentioned. Minimum compression tests were performed according to ABNT standards for walls closing blocks (fence). With that house built, we did studies of thermal performance in order to ascertain conditions of comfort, checking external and internal temperatures in the walls and in the ambient, among other variables, such as wind speed and relative humidity. The resulting blocks provided adequate thermal insulation to the environment, where the walls presented differences up to 11.7 ºC between the outer and inner faces, getting the maximum temperature inside the house around 31 °C, within the so-called thermal comfort zone for warm climates. At the end of the experiments it was evident the effectiveness of that construction in order to provide thermal comfort in the internal environment of the house, as well as we could confirm the viability of building houses from recyclable materials, reducing the constructive costs, becoming a suitable alternative for low- incoming families. Moreover, besides the low cost, the proposal represents an alternative use of various recyclable materials, therefore considered an ecological solution